2021
DOI: 10.1017/jfm.2020.1150
|View full text |Cite
|
Sign up to set email alerts
|

Do extreme events trigger turbulence decay? – a numerical study of turbulence decay time in pipe flows

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
(69 reference statements)
0
13
1
Order By: Relevance
“…The length Lz=100 of our tilted domain corresponds to an inter-band distance above which a band is considered as isolated, while the domain width Lx=6.6 is used because it corresponds to the natural spacing of streaks in channel flow in a 24 box [6,31]. For puffs in pipe flow, which are similar in many respects to the isolated bands considered here, Nemoto & Alexakis [21] conducted extensive computations showing that domain length had some effect on mean decay timescales, with L=50 and L=100 giving quantitatively different, but qualitatively similar results. Domain length is expected to have a quantitative effect on the splitting timescale; our domain length Lz=100 has been selected as a compromise between accuracy and computational cost.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The length Lz=100 of our tilted domain corresponds to an inter-band distance above which a band is considered as isolated, while the domain width Lx=6.6 is used because it corresponds to the natural spacing of streaks in channel flow in a 24 box [6,31]. For puffs in pipe flow, which are similar in many respects to the isolated bands considered here, Nemoto & Alexakis [21] conducted extensive computations showing that domain length had some effect on mean decay timescales, with L=50 and L=100 giving quantitatively different, but qualitatively similar results. Domain length is expected to have a quantitative effect on the splitting timescale; our domain length Lz=100 has been selected as a compromise between accuracy and computational cost.…”
Section: Methodsmentioning
confidence: 99%
“…In a study of the decay of turbulent puffs in pipe flow, Nemoto & Alexakis [21] found that the maximal vorticity over the domain followed a Fréchet distribution, a member of the Fisher–Tippett family. Moreover, they found that the parameters of this distribution depend linearly on Re over a range of 75 in Re near the critical value Rec.…”
Section: Extreme Value Description Of Decay and Splitting Trajectoriesmentioning
confidence: 99%
See 3 more Smart Citations